Walking with God through pain and suffering - Keller, Timothy, 1950- (Dutton, Penguin Group USA, 2013)
The problem of pain is a perennial one; and for those who undergo particular sufferings it can often be the largest obstacle for trusting in a good and loving God. If such a God exists, why is there so much suffering in the world? And how do we deal with it when it comes into our lives? In his fullest and most passionately argued book since 2008's bestseller The Reason For God, New York pastor and church planter Tim Keller brings his authoritative teaching, sensitivity to contemporary culture and pastoral heart to this pressing question, offering no easy answers but giving guidance, encouragement and inspiration.